CRITIQUE OF SEROLOGICAL AND ELECTROPHORETIC STUDIES ON THE INDIAN OIL SARDINE AND MACKEREL - George, Mangaly K (Indian Journal of Fisheries, 2011)
A method found to have been applied of late for fish population studies is the use of electrophoretic, biochemical and serological techniques in the identification of genetic stock as the natural units of fish resources (deLigny 1969, 1971, Eckroat 1973, Iwata 1973, Mangaly and Jamieson 1978 and Grant and Utter 1980). The common goal of these investigations is to describe the genetic composition of the sample population in terms of observed gene frequencies or genotype proportions. A standard procedure followed in all these studies involves detection of one or more suitable gene-marker in the form of electrophoretic variants or serological polymorphs, calculation of gene-frequencies or genotype proportions in the tested samples containing statistically sufficient number of specimens, comparison of the observed distribution pattern of different phenotypes with that expected pattern calculated, on the basis of a proposed genetic model, and interpretation of significant gene-frequency differences or zygotic proportions at one or more loci as indicative of heterogeniety of populations tested. Jamieson (1974) has focussed high-lights on these points.